Recurrent pregnancy loss: TNF-α and IL-10 polymorphisms - Amrit Kaur; Anupam Kaur (Wolters Kluwer Medknow Publications, 2011)
Background : The recurrent pregnancy loss requires careful consideration of genetic, anatomic, endocrine, infectious and immunological factors. Cytokine gene polymorphisms in the promoter regions of tumor necrosis factor (TNF)-α and interleukin (IL)-10 are associated with recurrent pregnancy loss. AIM: The aim of present study was to investigate the association of the IL-10 -592C/A and TNF-α-308 G/A, promoter polymorphisms among women with at least three consecutive miscarriages. Materials and Methods : Genotyping was done in 50 women with RPL for IL-10-592C/A and TNF-α-308G/A promoter polymorphism to see the association of these loci with pregnancy loss. The control group included 50 healthy women having two or more children (mean age of the female subjects 35 years) for statistical comparisons. Results : IL- 10-592C/A and TNF-α-308G/A promoter polymorphisms were not associated with the recurrent miscarriages. Conclusions : There is a need to screen a larger sample and in different ethnic groups using IL-10-592C/A and TNF-α-308G/A markers to understand their association with recurrent miscarriages. This would further help in efficient management of immunologically mediated recurrent miscarriages at the sample/individual level.